Acquired heart disease and pregnancy - Acho Mego, Segundo (2015)
This review attempts to highlight the importance of acquired heart disease pathophysiology, clinical features, diagnosis and treatment during pregnancy and childbirth, so that both obstetricians and specialist consultation, especially the cardiologist, provide adequate advice to the patient in terms of maternal and infant prognosis.